PABRA Narrative Annual Report: April 2011 – March 2012 - Pan-Africa Bean Research Alliance (Pan-Africa Bean Research Alliance, 2012)
The goal of the Pan-Africa Bean Research Alliance (PABRA) program is to improve nutrition, health, and food security, facilitate a resilient production system able to recover rapidly from adverse effects of environmental stresses, and address market challenges and therefore contribute sustainably to better livelihoods and incomes of resource-poor smallholder families in eastern, central, southern and western Africa. The achievements reported below are based on a five year (2009–2013) framework developed following a Joint External Evaluation of PABRA (JEEP) in 2007 and supported by both CIDA and SDC. The framework was reviewed in 2010; three outcome pillars were consolidated from the existing framework. These are: (I) increasing utilization of improved and marketable bean varieties, new crop management techniques and micro-nutrient rich bean based products particularly by women, (ii) increasing trade in a gender equitable manner, and (iii) increasing response to demands in the bean sector, and utilizing information and knowledge to influence bean policy in a gender equitable manner. The report highlights the key results and progress made towards targets at intermediate and immediate outcome as well as output levels. The targets were achieved through collaborative efforts by PABRA partners that include NARIs, NGOs, GOs, extension services providers and private sector.